Evaluation of 5H‐Thiazolo[3, 2‐α]pyrimidin‐5‐ones as Potential GluN2A PET Tracers. (3rd July 2020) - He, Yingfang; Whitehead, David M.; Briard, Emmanuelle; Numao, Shin; Mu, Linjing; Schibli, Roger; Ametamey, Simon M.; Auberson, Yves P.
Abstract: We describe here our efforts to develop a PET tracer for imaging GluN2A‐containing NMDA receptors, based on a 5 H ‐thiazolo[3, 2‐α]pyrimidin‐5‐one scaffold. The metabolic stability and overall properties could be optimized satisfactorily, although binding affinities remained a limiting factor for in vivo imaging. We nevertheless identified 7‐(((2‐fluoroethyl)(3‐fluorophenyl)amino)‐methyl)‐3‐(2‐(hydroxymethyl)cyclopropyl)‐2‐methyl‐5 H ‐thiazolo‐[3, 2‐α]pyrimidin‐5‐one ([ 18 F]7b ) as a radioligand providing good‐quality images in autoradiographic studies, as well as a tritiated derivative, 2‐(7‐(((2‐fluoroethyl)(4‐fluorophenyl)amino)methyl)‐2‐methyl‐5‐oxo‐5 H ‐thiazolo[3, 2‐α]pyrimidin‐3‐yl)cyclopropane‐1‐carbonitrile ([ 3 H2 ]15b ), which was used for the successful development of a radioligand binding assay. These are valuable new tools for the study of GluN2A‐containing NMDA receptors, and for the optimization of allosteric modulators binding to the pharmacophore located at the dimer interface of the GluN1‐GluN2A ligand‐binding domain. Abstract : New tools for GluN2A‐containing NMDA receptors have been discovered through the optimization of 5 H ‐thiazolo[3, 2‐α]pyrimidin‐5‐one derivatives. The radioligand [ 18 F]7b provided high‐quality images in autoradiographic studies, while its tritiated analogue [ 3 H2 ]15b allowed the development of a radioligand binding assay, useful for the study of GluN2A‐containing NMDA receptors and the optimization of allosteric modulators binding at the GluN1–GluN2A interface.